PHASE COMPOSITION AND MAGNETORESISTIVE PROPERTIES OF SENSOR ELECTRONIC ELEMENTS BASED ON MULTICOMPONENT FILM ALLOYS - Оdnodvorets, Larysa; Protsenko, Serhiy; Shumakova, Nataliya; Protsenko, Ivan (Collection of scientific papers «ΛΌГOΣ», 2023)
According to the generally accepted classification (see, for example, [1]), two-component alloys is a low-entropy alloys, with 3-4-components is a medium-entropy alloys and 5-14-componets alloys is a high-entropy (HEA) alloys. HEA can be formed based on Co, Ni, Fe and Cu, Cr, Al or Co, Ni, Fe and Ti, Zr, Hf or V, Nb, Ta, etc. [1].